Altered Corneal Innervation and Ocular Surface Homeostasis in FHV-1-Exposed Cats: A Preliminary Study Suggesting Metaherpetic Disease - Sebbag, Lionel; Thomasy, Sara M.; Leland, Adriana; Mukai, Madison; Kim, Soohyun; Maggs, David J. (Frontiers in Veterinary Science, 2021)
Metaherpetic disease is recognized in humans affected by herpes simplex virus-1 but is not reported in cats affected by feline herpesvirus-1 (FHV-1) despite the high prevalence of herpetic disease in this species and strong similarities in viral biology between alphaherpesviruses of humans and cats. This preliminary work evaluated cats naïve to FHV-1 (n=9 cats, 18 eyes; control population) and cats naturally exposed to FHV-1 (n=4 cats, 7 eyes), as confirmed by serologic testing and review of medical records. Ante-mortem assessment included clinical scoring, blink rate, corneal aesthesiometry, tear film breakup time (TFBUT), and Schirmer tear test-1 (STT-1) with or without the nasolacrimal reflex. Post-mortem assessment involved confocal microscopy of the corneas and evaluation of corneal nerves with ImageJ. Groups were compared with Student’s t tests and results are presented as mean±standard deviation. Compared to control, herpetic cats had significantly higher (P≤0.010) clinical scores (0.2±0.4 vs. 4.6±2.8) and response to nasolacrimal stimulation (7.8±10.8% vs. 104.8±151.1%), significantly lower (P<0.001) corneal sensitivity (2.9±0.6 cm vs. 1.4±0.9 cm), STT-1 (20.8±2.6 mm/min vs. 10.6±6.0 mm/min), TFBUT (12.1±2.0 sec vs. 7.1±2.9 sec), and non-significantly lower blink rate (3.0±1.5 blinks/min vs. 2.7±0.5 blinks/min; P=0.751). All parameters evaluated for corneal nerves (e.g., nerve fiber length, branching, occupancy) were notably but not significantly lower in herpetic vs. control cats (P≥0.268). In sum, cats exposed to FHV-1 had signs suggestive of corneal hypoesthesia and quantitative/qualitative tear film deficiencies when compared to cats naïve to the virus. It is possible these are signs of metaherpetic disease as reported in other species.